Eksplorasi Kualitatif Dinamika Komunitas Online: Pola Interaksi dan Pengaruhnya dalam Era Digital - Nur Alifia; Yulfa Lumbaa; Nur Riswandy Marsuki (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The dynamics within online communities are an interesting subject of exploration, especially when we consider the interaction patterns and their influence in the rapidly evolving digital era. This research aims to explore in depth the interaction patterns formed within online communities and analyze the influence of online communities on their members. This research uses a qualitative research method with a descriptive qualitative approach. Data collection methods will involve in-depth interviews, participant observation, and content analysis. Qualitative data will be analyzed using a thematic analysis approach. It was found that the dominating interaction patterns, such as in-depth discussions, exchange of experiences, and collaboration on joint projects, provide a solid foundation for intellectual growth and the development of personal relationships within the community.